A new approach for business process management enhancement: mobile hospital case study. (21st January 2022) - Limam, Hela; Bouderbela, Amal; Akaichi, Jalel
Nowadays, business process model and notation (BPMN) is the tool used to support business process management and business users to bridge the communication gap between business process design and implementation. However, the BPMN metamodel lacks formal specification of well-formed rules. In this context, we propose an object constraint language (OCL)-based approach to enhance the expressivity of the BPMN model to hold the information needed and to express resource allocation constraints. Furthermore, we propose an algorithm that verifies if the BPMN model has bad marks in order to verify the correctness of the enhanced model. The whole approach has been tested in the medical field. In particular, it has been used to model, check and improve the care process of a mobile hospital.